Outlines of a Cultural Strategy - Al-Alwani, Taha Jabir (International Institute of Islamic Thought, 1995)
This paper not only addresses the intellectual crisis in the Muslim world as manifested in the present state of Muslim thought, knowledge, education, and civilization a crisis which is directly responsible for the Muslim world's social, economic, and political problems but it also presents compelling and thoughtprovoking ideas for an alternative cultural strategy likely to alleviate the Ummah's malaise and benefit humanity at large. Dr. AlAlwani argues that the proposed cultural strategy has never been so urgent and imperative and must establish the Islamic world view with rational educational policies on the basis of firm principles and as farsighted strategy with the aim of dispelling the religious/secular disparity in education while keeping consistently in touch with our time.